Impact of Lactobacillus- and Bifidobacterium-Based Direct-Fed Microbials on the Performance, Intestinal Morphology, and Fecal Bacterial Populations of Nursery Pigs - Juan Castillo Zuniga; Anlly M. Fresno Rueda; Ryan S. Samuel; Benoit St-Pierre; Crystal L. Levesque (Microorganisms)
Weaning is a critical stage in the swine production cycle, as young pigs need to adjust to sudden and dramatic changes in their diet and environment. Among the various organ systems affected, the gastrointestinal tract is one of the more severely impacted during this transition. Traditionally, challenges at weaning have been managed by prophylactic use of antibiotics, which not only provides protection against diarrhea and other gut dysfunction but also has growth-promoting effects. With banning or major restrictions on the use of antibiotics for this purpose, various alternative products have been developed as potential replacements, including direct-fed microbials (DFMs) such as probiotics and postbiotics. As their efficiency needs to be improved, a continued effort to gain a deeper understanding of their mechanism of action is necessary. In this context, this report presents a study on the impact of a Lactobacillus-based probiotic (LPr) and a Bifidobacterium-based postbiotic (BPo) when added to the diet during the nursery phase. For animal performance, an effect was observed in the early stages (Day 0 to Day 10), as pigs fed diets supplemented with either DFMs were found to have higher average daily feed intake (ADFI) compared to pigs fed the control diet (p < 0.05). Histological analysis of intestinal morphology on D10 revealed that the ileum of supplemented pigs had a higher villus height/crypt depth ratio (p < 0.05) compared to controls, indicating a benefit of the DFMs for gut health. In an effort to further explore potential mechanisms of action, the effects of the DFMs on gut microbial composition were investigated using fecal microbial communities as a non-invasive representative approach. At the bacterial family level, Lactobacillaceae were found in higher abundance in pigs fed either LPr (D10; p < 0.05) or BPo (D47; p < 0.05). At the Operational Taxonomic Unit (OTU) level, which can be used as a proxy to assess species composition, Ssd-00950 and Ssd-01187 were found in higher abundance in DFM-supplemented pigs on D47 (p < 0.05). Using nucleotide sequence identity, these OTUs were predicted to be putative strains of Congobacterium massiliense and Absicoccus porci, respectively. In contrast, OTU Ssd-00039, which was predicted to be a strain of Streptococcus alactolyticus, was in lower abundance in BPo-supplemented pigs on D47 (p < 0.05). Together, these results indicate that the DFMs tested in this study can impact various aspects of gut function.